2016
DOI: 10.1177/0081246316682631
|View full text |Cite
|
Sign up to set email alerts
|

The influence of simultaneous interference and enrichment in work–family interaction on work-related outcomes

Abstract: This study aimed to determine how work–nonwork interference and work–family enrichment operate simultaneously to influence the work-related outcomes job satisfaction, organisational commitment, and subjective career success. By employing South African work–family instruments, the study tested substantive hypotheses in this regard. A cross-sectional survey design among a sample of permanently employed married parents (n = 212) was utilised. Statistical analyses included confirmatory factor analyses and validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 54 publications
(84 reference statements)
1
17
0
Order By: Relevance
“…Previous criterion-related validation studies on the MACE also provided support for the plausibility of the MACE-W2FE consisting of an essentially unidimensional construct as opposed to four distinct constructs (De Klerk et al, 2015;Koekemoer et al, 2017;Marais et al, 2014). It was found that the group-specific four-factor model showed moderate correlates (i.e.…”
Section: Substantive Findingsmentioning
confidence: 80%
See 3 more Smart Citations
“…Previous criterion-related validation studies on the MACE also provided support for the plausibility of the MACE-W2FE consisting of an essentially unidimensional construct as opposed to four distinct constructs (De Klerk et al, 2015;Koekemoer et al, 2017;Marais et al, 2014). It was found that the group-specific four-factor model showed moderate correlates (i.e.…”
Section: Substantive Findingsmentioning
confidence: 80%
“…The SO factor models showed that a strong common factor underlies the MACE-W2FE, which can be consistent with an approximate unidimensional factor model with trivial group-specific factors or a general factor underlying substantive groupspecific factors. Koekemoer et al (2017) and Marias et al (2014) did not indicate clearly which of the former or latter assumptions applied to the SO factor model reported. They argued that in the presence of multicollinearity, a goodfitting SO factor model justified the use of a single-aggregated variable in the exogenous part of an SEM model when supported in theory.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Within this sample, high internal consistency values for both the overall scale (Composite reliability: 0.91) and sub-dimensions (ranging from 0.77 to 0.92) were found. Previous studies reported acceptable Cronbach's alpha reliability values (Koekemoer, Strasheim, & Cross, 2017).…”
Section: Methodsmentioning
confidence: 91%